Design And Implementation of Freeradius as A User Manager on The Mikrotik Hotspot Network at PT Indotruck Utama using The NDLC (Network Development Life Cycle) Method - Pratama, Arya Pandu; Sugiyanta, Lipur; Idrus, Ali (IJISTECH (International Journal of Information System and Technology), 2023)
PT Indotruck Utama utilizes the 802.11n network only as an internet medium, without thinking about a sufficient security system for offices or companies. By only utilizing the 802.11n network which has poor security, it affects many illegal users who can enter the wireless network and can interfere with the performance of employees who are working. The purpose of this study is to produce a RADIUS-based authentication system that is used to improve wireless network security systems, namely being able to make a user have to login authentication twice, create different usernames and passwords for each user, prevent the entry of illegal users, and facilitate administrators in user management. In designing FreeRADIUS as a user manager on this proxy hotspot network using the NDLC (Network Development Life) method through 6 stages, namely analysis, design, simulation prototype, implementation, monitoring, and management. However, its application is only carried out until the implementation stage. This authentication system can be one solution to solve some problems that exist in the wireless network at PT Indotruck Utama. The test results from the capture on the wireshark application that uses PAP authentication still see the username and password, while those who use CHAP authentication only the username is visible, while the password is not visible because it has passed the encryption process.